Chicken Wing Training Model for Endoscopic Microsurgery - Jusue-Torres, Ignacio; Sivakanthan, Sananthan; Pinheiro-Neto, Carlos Diogenes; Gardner, Paul A.; Snyderman, Carl H.; Fernandez-Miranda, Juan C. (Journal of Neurological Surgery Part B: Skull Base, 2013)
Objectives To present and validate a chicken wing model for endoscopic endonasal microsurgical skill development.Setting A surgical environment was constructed using a Styrofoam box and measurements from radiological studies. Endoscopic visualization and instrumentation were utilized in a manner to mimic operative setting.Design Five participants were instructed to complete four sequential tasks: (1) opening the skin, (2) exposing the main artery in its neurovascular sheath, (3) opening the neurovascular sheath, and (4) separating the nerve from the artery. Time to completion of each task was recorded.Participants Three junior attendings, one senior resident, and one medical student were recruited internally.Main Outcome Measures Time to perform the surgical tasks measured in seconds.Results The average time of the first training session was 48.8 minutes; by the 10th training session, the average time was 22.4 minutes. The range of improvement was 25.7 minutes to 72.4 minutes. All five participants exhibited statistically significant decrease in time after 10 trials. Kaplan-Meier analysis revealed that an improvement of 50% was achieved by an average of five attempts at the 95% confidence interval.Conclusions The ex vivo chicken wing model is an inexpensive and relatively realistic model to train endoscopic dissection using microsurgical techniques.
Keywords: chicken wing dissection; endoscopic surgical skills; training model